Changes in Reading Skills After Learning Using Puzzle in the Kindergarten - Sari, Surya Mustika; Vidia, Henny (Universitas Islam Lamongan, 2021)
The ability to read is an academic substance that is difficult for early childhood to learn. One of the effective ways that can be applied in the process of learning to read in early childhood is by combining learning with play such as using puzzle media. The purpose of this study was to determine changes in reading skills after being given learning using puzzle media in children at Kindergarten, Sooko Village, Mojokerto Regency. In this study, the research design used was pre-experimental with one group pretest-posttest design. The population in this study were all 45 children in Kindergarten, Sooko Village, Mojokerto Regency. The sample in this study were 40 people. The independent variable in this study is the puzzle media. The dependent variable in this study is reading ability. The instrument used in this study was an observation sheet. The data analysis technique used is the Wilcoxon signed rank test. The results of this study indicate that respondents who experienced changes in reading ability in the good category were 9 respondents (50%), the sufficient category was 4 respondents (22.2%), and the less category was 5 respondents (27.8%). The results of statistical tests using the Wilcoxon signed rank test statistic showed sig. 0.001 < (0.05) then H0 is rejected and H1 is accepted, which means that there is a change in reading ability after being given learning to use reading puzzle media in children aged at Kindergarten, Sooko Village, Mojokerto Regency.